Case report: Effectiveness of Janus kinase inhibitors in the management of isolated noninfectious uveitis: a case series - Vidic Krhlikar, Nina; Tomšič, Matija; Jaki Mekjavić, Polona; Klobučar, Pia; Vidović Valentinčič, Nataša (Frontiers in Pharmacology, 2025)
PurposeThis study aimed to assess the efficacy of Janus kinase inhibitors (JAK-i) in the treatment of refractory isolated non-infectious uveitis.Case presentationWe examined a case series involving three patients with isolated non-infectious uveitis, who were managed between December 2019 and December 2023 at The Eye Hospital, University Medical Centre Ljubljana. The JAK-i therapy was initiated due to the patients’ unresponsiveness to disease-modifying antirheumatic drugs.OutcomesIn our case series, two patients presented with anterior and intermediate uveitis, one with posterior uveitis. None of the patients had any associated systemic disease. After the initiation of JAK-I therapy, all the patients achieved remission lasting for more than 1 year. No significant side effects were observed in any of the patients throughout a mean follow-up period of 31.6 months (range, 16–55 months).ConclusionIn this report, we present three cases of refractory isolated non-infectious uveitis successfully treated with JAK-i. This is the first report on the use of baricitinib and upadacitinib in this context. Our findings suggest that alternative use of JAK-i, apart from tofacitinib alone, may be an effective treatment option for such patients.